TINGKAT KEPERCAYAAN DIRI TERHADAP KEMAMPUAN DRIBBLING PADA PESERTA EKSTRAKURIKULER FUTSAL SISWA SMPN 4 AMUNTAI - Wahyudi, Muhammad Ibda; Ramadhan Arifin; Lazuardy Akbar Fauzan (Jurnal Pedagogik Olahraga, 2024)
This study aims to analyze the level of self-confidence among students participating in futsal extracurricular activities at SMPN 4 Amuntai and examine its relationship with dribbling skill performance. The study employs a descriptive quantitative approach, involving 16 students who completed a Likert scale questionnaire consisting of 20 statement items about self-confidence, and subsequently took a standardized dribbling skill test. The total score obtained from the self-confidence questionnaire reached 807 out of a maximum possible score of 1600, resulting in an achievement percentage of 50.44%—classified as "neutral" based on the Likert scale criteria used. Meanwhile, the results of the dribbling test showed that most students were in the "moderate" category (8 students), "poor" (3 students), and "very poor" (5 students), with none falling into the "good" or "very good" categories. These findings indicate that the students' dribbling skills are still relatively low and may be related to their less-than-optimal level of self-confidence. This underscores the importance of integrating affective and psychomotor aspects in physical education learning. Future studies are recommended to expand the sample size and develop a multidimensional self-confidence instrument, including measures of perceived competence and verbal encouragement.